The evolution of digital transformation in SMEs in the manufacturing industry in the different blocks of the BM Canvas since the beginning of the pandemic - Bednářová, Markéta; Tesařová, Mariana; Šimberová, Iveta (Business, Management and Economics Engineering, 2023)
Purpose – The following article focuses on assessment of the evolution of digital transformation in SMEs in the manufacturing industry since the beginning of the pandemic. The digital transformation is assessed in the different blocks of the BM Canvas. The main objective of the paper is to evaluate the impact of the pandemic on the development of digital transformation, and to assess whether it is still influencing it now, or vice versa, or no longer has such an impact. Research methodology – The digital transformation is examined in each block of the Business Model Canvas (BM Canvas) from the beginning of the pandemic to the current state. The individual data is obtained from a survey conducted among 18 SMEs. Small and medium-sized enterprises in the manufacturing industry are examined. The survey is based on semi-structured interviews with SME´s management representatives. The collected data is then processed by examining the average rate of digital transformation in each block, the modus, and the median. The focus was again on developments and changes in the digital transformation of enterprises. The data was collected for three periods – before the pandemic (2019), during the pandemic (2021) and now (July 2022). Findings – The paper shows the evolution of digital transformation in the different building blocks of the BM Canvas for SMEs in the manufacturing industry since the beginning of the pandemic. The evolution of digital transformation varies across the BM Canvas blocks. For the Channels block, as of July 2022, there has been a decrease in the average digital transformation rate. The other blocks have seen an increase and continue to develop. However, the increases are no longer as high as in 2021. Whether digital transformation will continue to develop for individual blocks in future periods is a suitable research question for further research. The findings show that the changes and developments vary from building block to building block. It was found that the importance of each building block changed during the pandemic for each firm representative. The results provide the basis for the analysis of the development and change of BM Canvas for individual companies. Research limitations – At the moment, the current situation in Ukraine, in addition to the COVID-19 pandemic, is playing a major role in SMEs activities as it affects companies. This conflict was not considered in the research, and the development since the beginning of the pandemic was followed. Practical implications – This research highlights how the digital transformation of individual SMEs in the manufacturing industry is evolving. It highlights the impact of the pandemic, which has undoubtedly increased the growth of digital transformation rates. For future research, these results can be very useful, as other influences on the rates of digital transformation can be investigated. Originality/Value – The research was carried out on the basis of primary data collected by the authors themselves. The data were processed and evaluated. The results of the research show how the level of digital transformation in different blocks of the BM Canvas has evolved from the beginning for each SME in the manufacturing industry.